A Basal Sauropodomorph (Dinosauria: Saurischia) from the Ischigualasto Formation (Triassic, Carnian) and the Early Evolution of Sauropodomorpha - Martinez, Ricardo N. (Public Library of Science, 2009)
BACKGROUND: The earliest dinosaurs are from the early Late Triassic (Carnian) of South America. By the Carnian the main clades Saurischia and Ornithischia were already established, and the presence of the most primitive known sauropodomorph Saturnalia suggests also that Saurischia had already diverged into Theropoda and Sauropodomorpha. Knowledge of Carnian sauropodomorphs has been restricted to this single species. METHODOLOGY/PRINCIPAL FINDINGS: We describe a new small sauropodomorph dinosaur from the Ischigualsto Formation (Carnian) in northwest Argentina, Panphagia protos gen. et sp. nov., on the basis of a partial skeleton. The genus and species are characterized by an anteroposteriorly elongated fossa on the base of the anteroventral process of the nasal; wide lateral flange on the quadrate with a large foramen; deep groove on the lateral surface of the lower jaw surrounded by prominent dorsal and ventral ridges; bifurcated posteroventral process of the dentary; long retroarticular process transversally wider than the articular area for the quadrate; oval scars on the lateral surface of the posterior border of the centra of cervical vertebrae; distinct prominences on the neural arc of the anterior cervical vertebra; distal end of the scapular blade nearly three times wider than the neck; scapular blade with an expanded posterodistal corner; and medial lamina of brevis fossa twice as wide as the iliac spine. CONCLUSIONS/SIGNIFICANCE: We regard Panphagia as the most basal sauropodomorph, which shares the following apomorphies with Saturnalia and more derived sauropodomorphs: basally constricted crowns; lanceolate crowns; teeth of the anterior quarter of the dentary higher than the others; and short posterolateral flange of distal tibia. The presence of Panphagia at the base of the early Carnian Ischigualasto Formation suggests an earlier origin of Sauropodomorpha during the Middle Triassic.